Answer:
<u>Given </u>
A
<u>Find the inverse of f(x):</u>
- x = 3 + 6f⁻¹(x)
- 6f⁻¹(x) = x - 3
- f⁻¹(x) = (x - 3) / 6
B
- f · f⁻¹( ∛5/6) =
- f( f⁻¹( ∛5/6)) =
- f((∛5/6 - 3)/6) =
- 3 + 6((∛5/6 - 3)/6) =
- 3 + ∛5/6 - 3 =
- ∛5/6
C
- f · f⁻¹(x) =
- f(f⁻¹(x)) =
- f((x - 3)/6) =
- 3 + 6(x - 3)/6 =
- 3 + x - 3 =
- x
Answer:
The one you have selected is the right answer 126 times pi
Step-by-step explanation:
Exact answer - 395.840674
Answer:
s=4& c=7
Step-by-step explanation:
3(4)+9(7)=$75
8(4)+5(7)=$67
Answer:
60 marbles in total
Step-by-step explanation:
Find how many marbles there are in total by dividing 42 by 0.7:
42/0.7
= 60
So, there are 60 marbles in total